Feeling Capable and Worthy? Impact of Employee Silence on Self-Concept: Mediating Role of Organizational Citizenship Behaviors. Issue 1 (February 2021) - Chou, Shih Yung; Chang, Tree
While existing research findings have highlighted the consequences of employee silence at the interpersonal and organizational levels, little is known about how employee silence influences an employee's inferences of self. Drawing on a cross-organizational sample of 142 employees, we test the impact of employee silence, in the forms of acquiescent, quiescent, prosocial, and opportunistic silence, on employees' job self-efficacy and organization-based self-esteem. In addition, we examine how organizational citizenship behavior toward the organization and toward individuals mediates the direct effects. Results indicate that quiescent silence negatively affects organization-based self-esteem, and that opportunistic silence has a negative impact on job self-efficacy. In addition, organizational citizenship behavior toward the organization and organizational citizenship behavior toward individuals fully mediate the relationship between opportunistic silence and organization-based self-esteem, whereas organizational citizenship behavior toward individuals and organizational citizenship behavior toward the organization partially mediate the relationship between opportunistic silence and job self-efficacy. Implications for theory and practice are discussed.